Managing your feelings at work, for a reason: The role of individual motives in affect regulation for performance-related outcomes at work - Bindl, U.K.; Parker, Sharon; Sonnentag, S.; Stride, C.B. (WILEY, 2022)
Affect regulation matters in organizations, but research has predominantly focused on how employees regulate their feelings. Here, we investigate the motives for why employees regulate their feelings. We assess employees' engagement in affect regulation based on distinct motives and investigate their implications for performance-related outcomes. We develop a framework and measure for distinct types of motivated affect regulation at work, comprising hedonic affect regulation (motive to feel better), task-related affect regulation (motive to reach an achievement-related goal), and social affect regulation (motive to get along with others). Study 1 (N = 621 employees) indicated each type of motivated affect regulation was distinct from the others. In Study 2 (N = 80 employees; n = 821 observations), in line with our theorizing, hedonic and task-related affect regulation were both positively associated with performance-related outcomes via perceived affect-regulation success. In addition, the link between task-related affect regulation and perceived affect-regulation success was strongest for those individuals who habitually engage in deep acting. By contrast, social affect regulation did not predict perceived affect-regulation success or performance-related outcomes. Understanding why employees choose to manage their feelings advances insights on individual motives in employee behavior and provides new avenues for improving performance outcomes in organizations.